Beatfrost Clothing Enterprise / Muhammad Amirul Razin Roslan ... [et al.] - Roslan, Muhammad Amirul Razin; Jasmay, Ahmed Danial; Hamdan, Hasnizah; Mohd. Naseron, Muhammad Arief Hakimi; Saleh Uddin, Mohammad Shafiq; Kepli, Muizzatun Nasirah (2015)
BEA TFROST ENTERPRISE is a company which focuses on clothing production in Malaysia. Since here are so many local brand exist in Malaysia. We want to make the name of Malaysia become popular in becoming the new trendy and branded clothes. Differences in size, colours and type of fabric make this clothes looks interesting and suitable to all consumers. The affordable price and the comfortable gives an opportunity to this clothes to be one of marketable product a people love simple things and affordable. Moreover, the simple design and high quality of fabric give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decided to make some innovation by implying our creativity and modern element in this clothes. Nowadays, various type of clothes is one of the important things in any products making so we not only producing a shirt but we are producing eat shirt, cap, bags, long sleeves shirt, quarter sleeves shirt and sleeveless shirt. So, the customers n have various choice. We have done some research that Malaysia is one of developed country advanced in fashion and most of the Malaysians love to wear local brand shirt nowadays.